Formation of Nonionic Branched-Chain Glycolipids Nano-Emulsion for drug delivery systems - Ahmad, Noraini; Ramsch, Roland; Llinas, Meritxell; Solans, Conxita; Hashim, Rauzah; Tajuddin, Hairul Anuar (2014)
The effect of incorporating new nonionic glyco lipid surfactants on the properties of a model water/nonionic surfactant/oil nano-emulsion system was investigated using branched-chain alkyl glycosides : 2-hexyldecyl-p(la)-D -glucoside (2-HDG) and 2-hexyldecyl-p(la)-D -maltoside (2-HDM), whose structures are closely related to glycero-glycolipids. Both 2-HDG and 2-HDM have an identical hydrophobic chain (C 16), but the former consists a monosaccharide glucose head group, in contrast to the latter which has a disaccharide maltose unit. Consequently, their hydrophilic-lipophilic balance (HLB) is different. The results obtained have shown that these branched-ehain alkyl glycosides affect differently the stability of the nano-emu lsions. Compared to the model nanoemulsion, the presence of 2-HDG reduces the oil droplet size, whereas 2-HDM modify the properties of the model nano-emulsion system in terms of its droplet size and storage time stability at high temperature. These nano-emulsions have been proven capable of encapsulating ketoprofen, showing a fast release of almost 100% in 24 hours . Thus, both branched-chain alkyl glycosides are suitable as nano-cmulsion stabilizing agents and as drug delivery systems in the future .